Collective Power to Create Political Change: Increasing the Political Efficacy and Engagement of Social Workers. Issue 3 (3rd July 2017) - Ostrander, Jason A.; Lane, Shannon; McClendon, Jennifer; Hayes, Crystal; Smith, Tanya Rhodes
ABSTRACT: Because social workers are called to challenge social injustices and create systemic change to support the well-being of individuals and communities, it is essential that social workers develop political efficacy: belief that the political system can work and they can influence the system. This study explored the impact of an intensive political social work curriculum on political efficacy and planned political engagement among social work students and practitioners. The findings suggest this model of delivering a political social work curriculum effectively increases internal, external, and overall political efficacy, and that increasing political efficacy has promise for increasing future political engagement.